HUMAN EQUALITY REGARDLESS OF RACE OR ETNIA: A CASE STUDY OF ROMA COMMUNITY IN ALBANIA, DURRËS CITY - Kalemi, Ramiola (European Scientific Journal, ESJ, 2013)
The problem faced by Roma community in Albania has been well known for years; thus their current status is dependent on different specifications which form the vicious circle from where it is difficult to get out. This paper will make a multidimensional evaluation that includes the legal aspect, health, and the current conditions of life, of this target group of people who live in one of the greatest city of Albania which is Durres.